Search for a standard-model-like Higgs boson with a mass in the range 145 to 1000 GeV at the LHC - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; et al. (SPRINGER, 2013)
A search for a standard-model-like Higgs boson in the H -> WW and H -> ZZ decay channels is reported, for Higgs boson masses in the range 145 < m(H) < 1000 GeV. The search is based upon proton-proton collision data samples corresponding to an integrated luminosity of up to 5.1 fb(-1) at root s = 7 TeV and up to 5.3 fb(-1) at root s = 8 TeV, recorded by the CMS experiment at the LHC. The combined upper limits at 95 % confidence level on products of the cross section and branching fractions exclude a standard-model-like Higgs boson in the range 145 < m(H) < 710 GeV, thus extending the mass region excluded by CMS from 127-600 GeV up to 710 GeV.
Keywords: PARTON DISTRIBUTIONS; BROKEN SYMMETRIES; WEAK-INTERACTIONS; HIGH-ENERGIES; COLLIDERS; PHYSICS